Will policy to constrain GP referrals damage health? Evidence using practice level NHS emergency admissions administrative data - McCormick, B; Nicodemo, C; Redding, S (Elsevier, 2021)
Attempts to control hospital expenditure by managing down General Practitioner (GP) referrals are reoccurring features of UK health policy. However, despite the best efforts of GPs to benchmark referral criteria, patient health may be damaged and other costs created by constraining referrals to targets. This paper adopts an indirect method to indicate whether rationing practice referrals may damage population health by distorting the use of health resources away from patients' interests. We utilise a comprehensive database at practice level that allows us to explore the relationship between referrals and emergency admissions, using a panel fixed effects model of admissions that allows for the endogeneity of referrals. We find that practice referrals are positively and partially correlated with emergency admissions, which is consistent with time-varying practice-level sickness shocks driving the relationship between referrals and emergency care, rather than shocks to the practice willingness to refer, or to system reforms. In this environment, government policy to constrain referrals may make the elective care less responsive to practice-level variations in illness, and thereby lower health.